Features of Preparation of Fine Art Teachers in Modern Conditions - Abdullaev Sayfulla Faizullayevich; Shodieva Saodat Bobokulovna (International Journal on Orange Technologies, 2021)
The author of the article in the framework of the direction of education "Fine Arts" considers the tasks of training teachers of the fine arts in modern conditions. At the present stage of development of the education system of the Republic of Uzbekistan and the National Program for Personnel Training, taking into account the realities and requirements of society, the solution of the problems of high-quality training of teachers of higher and secondary schools acquires great, truly state significance